Coastal resources management Ulugan Bay, Palawan Island, the Philippines. - Fazi, Stefano; Flewweling, Peter (United Nations Educational Scientific and Cultural Organization, 2001)
Contents: vol.1 Ecology, culture and socio-economics.vol.2 Master plan for community based eco-tourismvol.3 An integrated management model.